Comparative analysis of the post caloric nystagmus with two and four stimulations by means of the vectoeletronistagmography - doi:10.5020/18061230.2004.p135 - Almeida, Renata Parente de (2012)
Vertigo is one of the most common symptoms nowadays and its diagnosis is based on the patient’s clinical history and on the otoneurological exam. This study aimed at analyzing the vestibular dysfunction diagnosis efficacy by using only cold caloric irrigation in vectoeletronistagmography. A retrospective survey of 174 vectoeletronistagmography exams from patients of the Audiology sector of Nucleo de Atenção Médica Integrada (NAMI) in the University of Fortaleza was done, by comparing the results with two and four irrigations. From the analysed exams, 64 (36,78 %) were symmetrical only with the single caloric irrigation (cold water) and 110 (63,22 %) were not. This kind of procedure is not efficient for the diagnosis, but it can be useful for screening, although a new study is necessary for validation